Kombinasi Expected Return dan Risiko Melalui Diversifikasi Saham LQ 45 Dalam Rangka Pemilihan Investasi Saham Di bursa Efek Indonesia Melalui Pembentukan Portofolio Optimal: Combination of Expected Return and Risk Through LQ 45 Stock Diversification in the Context of Selecting Stock Investments on the Indonesian Stock Exchange through the Establishment of an Optimal Portfolio - Hariyanto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is to determine the combination of expected return and LQ-45 stock risk in order to select investment in Indonesian Stock Exchange through the establishment of an optimum portfolio. The population of this study are pharmaceutical companies listed in the Indonesian Stock Exchange year 2008-2013. This research applied quantitative approach, with purposive sampling. The population consists of 14 LQ-45 stocks from February 2012-January 2015 period. The analytical technique used are (1) calculation of return of expectation and risk of stock, (2) calculation of stock selection entered in optimum portfolio, 3) calculation of optimum portfolio formation. The result of this research shows that the optimum portfolio formation in LQ-45 shares will determine portfolio exposure of 0.1835 and portfolio risk of 0.0104, which was obtained from Kalbe farma and Gajah Tunggal shares.